MICRONIZED EUTECTIC MIXTURE OF FENOFIBRIC ACID-SACCHARIN FORMATION FOR SOLUBILITY AND DISSOLUTION ENHANCEMENT - HASANAH, USWATUL; WAHYUNI, LIZA; ZAINI, ERIZAL (International Journal of Applied Pharmaceutics, 2023)
Objective: This study aims to increase the solubility and dissolution rate of fenofibric acid by forming a micronized eutectic mixture of fenofibric acid-saccharin with spray drying technique. Methods: Suspension of the eutectic mixture was prepared in ethanol: distilled water (3:1) followed by a spray drying method to obtain the microparticles. Microparticles characterization was performed by particle size analysis (PSA), powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC), FT-IR spectroscopy, and scanning electron microscopy (SEM). Solubility test was carried out in CO2-free distilled water, meanwhile the dissolution rate study was conducted in phosphate buffer solution at pH 6.8. Results: The results showed the mean of the samples’ particle size was 72.29±7.33 µm. Compared to the intact fenofibric acid, the micronized eutectic mixture sample has a decreased melting point, fusion enthalpy, and crystallinity without any wavenumber shifted in the FT-IR spectra. The solubility of micronized eutectic mixture was 2.2 times higher than intact fenofibric acid, while the amount of micronized eutectic mixture dissolved at 60 min was 11.7 times higher. Conclusion: It can be concluded that the spray-dried micronized eutectic mixture of fenofibric acid-saccharin was having the ability to enhance the dissolution of fenofibric acid.